2016
DOI: 10.7554/elife.20762
|View full text |Cite
|
Sign up to set email alerts
|

Frazzled promotes growth cone attachment at the source of a Netrin gradient in the Drosophila visual system

Abstract: Axon guidance is proposed to act through a combination of long- and short-range attractive and repulsive cues. The ligand-receptor pair, Netrin (Net) and Frazzled (Fra) (DCC, Deleted in Colorectal Cancer, in vertebrates), is recognized as the prototypical effector of chemoattraction, with roles in both long- and short-range guidance. In the Drosophila visual system, R8 photoreceptor growth cones were shown to require Net-Fra to reach their target, the peak of a Net gradient. Using live imaging, we show, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 49 publications
4
72
0
Order By: Relevance
“…Our studies show that netrin1 closely associates with the laminin along the pial surface of the spinal cord, to establish a local growth substrate for axons. This result is consistent with previous studies demonstrating that netrin1 acts locally in other systems (Akin and Zipursky, 2016; Baker et al, 2006; Brankatschk and Dickson, 2006; Deiner et al, 1997; Timofeev et al, 2012). While our model is inconsistent with the observations that netrin1 appears to act as graded diffusible chemoattractant in in vitro assays, it is noteworthy that these assays usually require ECM components, such as laminin or collagen for axon extension (Hazen et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our studies show that netrin1 closely associates with the laminin along the pial surface of the spinal cord, to establish a local growth substrate for axons. This result is consistent with previous studies demonstrating that netrin1 acts locally in other systems (Akin and Zipursky, 2016; Baker et al, 2006; Brankatschk and Dickson, 2006; Deiner et al, 1997; Timofeev et al, 2012). While our model is inconsistent with the observations that netrin1 appears to act as graded diffusible chemoattractant in in vitro assays, it is noteworthy that these assays usually require ECM components, such as laminin or collagen for axon extension (Hazen et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…Notably, studies in the Drosophila nerve cord and visual system have shown that membrane-tethered netrin was sufficient to rescue axon guidance defects in netrinA/B mutants (Brankatschk and Dickson, 2006; Timofeev et al, 2012). Recently, studies using live imaging in the visual system have demonstrated that target-derived netrin1 is required to attach growth cones to source cells (Akin and Zipursky, 2016). However, despite significant progress understanding netrin-mediated axon guidance, it has not been resolved whether netrin1 acts from the FP as a diffusible chemoattractant in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent to its own targeting, L3 produces the secreted attractant netrin, which influences R8 growth cones as they actively extend to this same layer [48]. Recent live imaging results show that netrin signaling stabilizes R8 terminals in the target area, but does not target R8 axons per se , similar to the stabilizing function of CadN for R7 [49]. Interestingly, R cell growth cones in turn produce a ligand (jelly belly) that is required for L3 survival, and therefore maintenance of R8 targeting [50].…”
Section: The Role Of Layers and Laminae For Synaptic Specificationmentioning
confidence: 99%
“…Membrane-bound netrin1 can rescue the loss of netrinA/B in the Drosophila nerve cord (Brankatschk and Dickson, 2006; Keleman and Dickson, 2001) and visual system (Timofeev et al, 2012). Other studies have suggested a local, adhesive role for netrin, attaching growth cones to source cells in the developing medulla (Akin and Zipursky, 2016). Moreover, our recent studies in the spinal cord (Varadarajan et al, 2017), with those in the hindbrain (Dominici et al, 2017), have revisited the role of FP-derived netrin1 in axon guidance.…”
Section: Introductionmentioning
confidence: 98%